THE ROLE OF MICROFINANCE IN POVERTY ALLEVIATIONS: CASE STUDY INDONESIA - Mohammad Zeqi Yasin (Universitas Airlangga, 2020)
The debate on whether microfinance genuinely alleviates poverty has captivatedmany researchers to investigate this issue. The results are mixed up and varied.Hence, this study aims to convey how the schemes of microfinance can deal with poverty, especially in Indonesia. Moreover, this study also investigates thesustainability of microfinance institutions in dealing with the trade-off betweensocial goal and profit goal. This study employs a descriptive analysis approach with literature study data collection technique. The discussion of this study reveals that the emergence of microfinance in Indonesia, in any ways, has had a significant role as a source of income for poor or micro entrepreneurs. The schemes of conventional and Islamic have also diversified opportunity to gain funding. However, the mix possible success of microfinance, either high-profit goal or high-social goal, have to be seriously concerned. In this regard, the finding implication of this study is that the management structure requires new approaches to avoid such possible mix results. As the involvement of microfinance with most of unexperienced debtors, microfinance institutions as creditor have to, at least, not only provide financial help for the poor, but also offer non-financial help such as training and good relationship. This can be organized along with extending the deeper credit outreach, even if, for absolute poor.